Self – sufficiency Professionalism and its relationship to job satisfaction - حمزة علي ليث (Journal of College of Education, 2020)
The present research aims at identifying the Self – sufficiency Professionalism and its relation to job satisfaction among the employees of the government departments (Qadisiyah University employees as a model), as the number of the sample of the research sample was (200) male and female employees who were randomly selected in an equal manner. To measure this goal was built a Scale of Self – sufficiency Professionalism, which is the final form of (20) paragraphs, as the researcher built a Scale of job satisfaction, which is the final form of (18) paragraphs, has been extracted psychometric characteristics of both scales, such as Validity and Reliability and the use of appropriate statistical methods to extract Current search results. The most important results of the present research indicate that the employee at the University of Qadisiyah enjoy a high level of Self – sufficiency Professionalism, and that there is no statistically significant differences in Self – sufficiency Professionalism attributable to the type of owners (temporary contract employee - employee on permanent staff),The research also found a high level of job satisfaction among employees, and the existence of statistically significant differences in job satisfaction according to the type of staff (temporary contract employee - employee on permanent staff) attributed to the benefit of employees on permanent staff, as the current research has found a correlation Positive between both Self – sufficiency Professionalism and job satisfaction among the staff of the University of Qadisiyah, the research came up with a series of recommendations and important proposals.